Context and mitigation of lost circulation during geothermal drilling in diverse geologic settings. (February 2023) - Winn, Carmen; Dobson, Patrick; Ulrich, Craig; Kneafsey, Timothy; Lowry, Thomas S.; Akerley, John; Delwiche, Ben; Samuel, Abraham; Bauer, Stephen
Highlights: Lost circulation while drilling for geothermal energy development drives up drilling costs. Four geologically distinct geothermal fields were examined in detail. Lost circulation was frequently encountered after an increase in secondary mineralization, indicative of fluid flow and fracturing or faulting. Mitigation strategies include using lost circulation materials and cement plugs in the shallow nonproductive zone, and drilling blind often with an air assist in the reservoir. Abstract: Lost circulation is one of the most common and expensive problems facing geothermal energy development, representing up to 30% of drilling costs. We examined drilling records from four geothermal fields—McGinness Hills in central Nevada, Don A. Campbell and Steamboat Hills in western Nevada, and Puna Geothermal Venture on the Big Island of Hawai'i— to identify geologies most prone to lost circulation, as well as common mitigation strategies. Depths of lost circulation events varied, but their frequency often increased in the production interval. Lost circulation commonly occurred near fault intersections, and heavily faulted fields like McGinness Hills and Don A. Campbell showed secondary mineralization within approximately 100 m (328 ft) or less of where circulation was lost. Lost circulation mitigation strategies included using locally available materials (e.g., cotton seed hulls) as well as more expensive proprietary lost circulation materials, cement plugs above the reservoir, and drilling blind with aerated, polymer-based mud in the production zone. Addressing lost circulation using a well thought out decision-making approach and materials above the reservoir will save time and cost, and provide needed well integrity. Mitigation often requires a series of steps, typically applied from perceived least expensive to most, and are dependent on the severity and location in the well where circulation was lost and availability of materials. Placing cement plugs can cure lost circulation events, however these plugs are often expensive, time-consuming, and may not be successful.